Penerapan Teknologi Dalam Pelatihan Pembuatan E- Modul Untuk Mengintegrasikan Budaya Lokal - Wulandari, Selvi; Harun, Fauzia; Rahmadani, Andi; C. Flori, Jein; Suleman, Sriwildasari; Srinawari, Risna (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
In the context of education in Indonesia, fostering love and pride for local culture is crucial. Our country has a vast cultural diversity that, if not preserved and introduced from an early age, could be lost to the tides of modernization. Therefore, the role of teachers as strategic agents in the educational process must be encouraged to adopt more innovative approaches in teaching. This community service aims to equip teachers with the skills to create e-modules that integrate local cultural values as part of the learning process. The activities were conducted in May 2025, involving 14 teachers from SMA Negeri 11 Halmahera Selatan. The training procedure included planning, implementation, and evaluation stages. Evaluation results showed a significant improvement in teachers' understanding of local culture and technical skills, reflected in the average pretest and posttest scores, which increased from 61.4% to 90% for cultural understanding and from 58.6% to 80.3% for digital application skills. The resulting e-modules were able to present material aligned with regional characteristics, facilitating more engaging and interactive learning. This training outcome is expected to support the improvement of learning quality through culturally relevant digital media while strengthening the preservation of local culture within education. Integrating local culture into e-modules is also expected to enhance students' learning interest and critical thinking regarding cultural values.